2020
DOI: 10.1155/2020/8823498
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cowpea (Vigna unguiculata (L.) Walp.) Mutant Lines for Drought Tolerance

Abstract: Cowpea provides the cheapest source of protein with an average range of protein content of 23–30%. However, cowpea growth, development, and yield are greatly affected by drought during flowering and pod filling in the sub-Sahelian areas. The best way to cope with this situation is to develop drought-tolerant cowpea varieties. The objective of this study was therefore to evaluate cowpea lines developed through mutagenesis using gamma radiation to assess their reaction under optimal and water-stressed conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This suggested that gamma rays showed high mutagenic efficacy that leads to the creation of heterogeneous populations in the background of the three parental cultivars. Similar results were found by Senapati and Misra [42] and Kuralarasan et al [43] in blackgram, Das and Baisakh [44] in mungbean, and Gnankambary et al [45] in cowpea. The yield-related traits contribute reasonably to total genetic variation among the mutagenized population revealed by loading plot values in PCs.…”
Section: Discussionsupporting
confidence: 88%
“…This suggested that gamma rays showed high mutagenic efficacy that leads to the creation of heterogeneous populations in the background of the three parental cultivars. Similar results were found by Senapati and Misra [42] and Kuralarasan et al [43] in blackgram, Das and Baisakh [44] in mungbean, and Gnankambary et al [45] in cowpea. The yield-related traits contribute reasonably to total genetic variation among the mutagenized population revealed by loading plot values in PCs.…”
Section: Discussionsupporting
confidence: 88%
“…Temperatures above 35 0 C, which were recorded at the foliar level, intensified the thermohydric stress, the cowpea varieties reacting by reducing the photosynthesis process and intensifying the sweating process. Compared to 2020, in 2021, when higher temperatures were recorded in the air, the daily accumulation rate of CO2 through the photosynthesis process was lower by 6.91 µmol CO2/m 2 /s, and water losses through sweating were also lower by 0.72 mmol H2O/m 2 /s due to stomatal closure Due to the plant's biological properties, increased drought resistance and low soil fertility requirements, cowpea can be a good alternative to bean and soybean crops, which are very sensitive to stressors in areas with excessive drought (Drăghici, 2018, Gnankambary et. al., 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis is one of the popular techniques for increasing genetic diversity for crop development. Gamma‐ray mutation has been employed to improve the genetic diversity of cowpea in Burkina Faso (Gnankambary et al., 2020) and Namibia (Horn et al., 2016).…”
Section: Introductionmentioning
confidence: 99%